The Role of Leadership Style in Organizational Culture and Competence to Improve Village Fund Management Accountability - Moh. Ubaidillah; Mahesti Cahayuni (Profesional Muda Cendekia Publishing, 2022)
This research aims to find out and obtain empirical evidence about the influence of organizational culture and competence on the accountability of village fund management with leadership style as a moderation variable. The sampling in this study used purposive sampling method that produced a sample of 90 village treasurers from 18 districts of Magetan district. This research data analysis method uses Structural Equation Modeling (SEM) analysis with Partial Least Squares (PLS). The results showed that the competence and culture of the organization had a positive effect on the accountability of village fund management. Leadership style is able to moderate the influence of organizational culture and competence on the accountability of village fund management positively and significantly.